Writing with scripture: scripturalized narrative in the Gospel of Mark - Vette, Nathanael (Library of New Testament studies, 2022)
"Nathanael Vette proposes that the Gospel of Mark, like other narrative works in the Second Temple period, uses the Jewish scriptures as a model to compose distinctive episodes of Christ's life and tell a new story"--